Distally based sural flaps for soft tissue defects following traumatic osteomyelitis of lower leg and foot - Shunhong Luo; Yingliang Jiang; Zhonggen Dong; Xiao Peng; Shimu Shi; Zhaobiao Luo; Shibin Tao; Jianwei Wei (Scientific Reports, 2024)
Abstract This retrospective study aimed to determine the incidence and risk factors for osteomyelitis recurrence and present our experiences in treating traumatic osteomyelitis in the lower leg and foot. We retrospectively reviewed data from 174 patients with distally based sural flaps for treating traumatic osteomyelitis with soft tissue defects in the lower leg and foot from November 2003 to February 2021. Possible risk factors for osteomyelitis recurrence were compared between the osteomyelitis control and recurrence groups. A total of 162 (93.1%) flaps survived uneventfully, while 12 (6.9%) flaps developed partial necrosis. Five patients had a bone defect with an average length of 5 cm. The free vascularized bone grafts were performed in two patients, and bone transportations were performed in three patients. All patients were followed up with an average period of 72.8 months. There were 152 patients (87.4%) in control group and 22 patients (12.6%) in recurrence group. The recurrence rates of osteomyelitis were significantly higher when the patient’s age was 40 years or more and the duration was 10 weeks or more (P < 0.05). Cierny-Mader (C-M) classification type IV osteomyelitis was also significantly associated with osteomyelitis recurrence (p = 0.049). This flap combined with appropriate osteomyelitis treatment was an effective method to treat traumatic osteomyelitis of lower leg and foot with a soft tissue defect. Both patient age ≥ 40 years old and C-M type IV osteomyelitis were nonnegligible risk factors for osteomyelitis recurrence.